SPE Middle East Oil &Amp; Gas Show and Conference 2015
DOI: 10.2118/172564-ms
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence Based Estimation of Water Saturation Using Electrical Measurements Data in a Carbonate Reservoir

Abstract: Good estimation of water saturation is necessary for successful estimation of reservoir properties as it minimizes the error in initial oil-in-place calculations. Electrical measurements on core plugs have been used to predict water saturation by analyzing the parameters of Archie's equation. Presently, several methods such as conventional, CAPE (1, m, n), CAPE (a, m, n) and 3D methods have been used to analyze the parameters. However, the accuracy of these methods has become inadequate for optimal estimations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…The results showed that ANFIS provided slightly better output accuracy than ANN. Meanwhile, ANN and FL were compared by Bageri et al [114] in a carbonate reservoir in the Middle East. The output suggests that the FL model offers higher accuracy than the ANN model.…”
Section: Water Saturation Predictionmentioning
confidence: 99%
“…The results showed that ANFIS provided slightly better output accuracy than ANN. Meanwhile, ANN and FL were compared by Bageri et al [114] in a carbonate reservoir in the Middle East. The output suggests that the FL model offers higher accuracy than the ANN model.…”
Section: Water Saturation Predictionmentioning
confidence: 99%
“…However, in this context the dominant focus is Reservoir modelling & Characterization, e.g. [55]- [57] and Completion & Production related applications, e.g. [58]- [61].…”
Section: Bda: An Oil and Gas Industry Reviewmentioning
confidence: 99%
“…It was used by Bageri, Anifowose, and Abdulraheem (2015), Helmy, Fatai, and Faisal (2010), Imam, Anifowose, and Azad (2015), Khoukhi and Albukhitan (2010), nooruddin, Anifowose, and Abdulraheem (2013), olatunji, Selamat, and raheem (2011), and oloso, Khoukhi, Abdulraheem, and Elshafei (2010). Bageri et al (2015) used the predictive capabilities of Ann and the Fuzzy Inference Engine to predict the water saturation of a Middle Eastern carbonate petroleum reservoir. utilised the capabilities of data mining and CI in the prediction of porosity and permeability based on the hybridisation of fuzzy logic, SVM, and functional networks (Fn).…”
Section: Conventional Stratification Strategiesmentioning
confidence: 99%